Synthesis of bio-compatible SPION-based aqueous ferrofluids and evaluation of radiofrequency power loss for magnetic hyperthermia - Mary, Antony P. Reena; Narayanan, T. N.; Sunny, Vijutha; Sakthikumar, D.; Yoshida, Yasuhiko; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Nanoscale Research Letters, 2010)
Bio-compatible magnetic fluids having high saturation magnetization find immense applications in various biomedical fields. Aqueous ferrofluids of superparamagnetic iron oxide nanoparticles with narrow size distribution, high shelf life and good stability is realized by controlled chemical co-precipitation process. The crystal structure is verified by X-ray diffraction technique. Particle sizes are evaluated by employing Transmission electron microscopy. Room temperature and low-temperature magnetic measurements were carried out with Superconducting Quantum Interference Device. The fluid exhibits good magnetic response even at very high dilution (6.28 mg/cc). This is an advantage for biomedical applications, since only a small amount of iron is to be metabolised by body organs. Magnetic field induced transmission measurements carried out at photon energy of diode laser (670 nm) exhibited excellent linear dichroism. Based on the structural and magnetic measurements, the power loss for the magnetic nanoparticles under study is evaluated over a range of radiofrequencies.
Keywords: Magnetic heating; Magnetic hyperthermia; Magnetic relaxation; Power loss; Superparamagnetism